(untitled) (Conferencea, 2022)
As you know, in all organ systems in the body there are diseases that are inherent in a certain number. The prevention and treatment of these diseases will be the responsibility of young future doctors like us. For example the nerf system.One of the most common cases of disease in this system is : it is associated with the conduction of nerf impulses. In particular , when something iodine affects the body, it is received through receptors located in the impulse skin, tam cognition, sense of smell, hearing, sight and hakozo organs, transmitting it to the brain centers of the head and orq. This impulse goes through many places to reach the center , but this process occurs extremely quickly that is, it moves at speeds from 4.4 meters per second to 100 meters per second. These nerf impulses are studied by reaching the center and transmitted to the working organs.The working body performs work under the influence of this incoming impulse.